Assessment on the Effect of Rapid Urbanization on Groundwater Quality of Mirpur Area, Dhaka City, Bangladesh - Sumaiya Akter, Mili; S. M. Mahmudur, Rahman; A. B. M. Kamal, Pasha; Md. Azharul Haque, Chowdhury (INTI International University, 2024)
Dhaka’s population is increasing day by day as more people are migrating towards Dhaka city for improving their level of living and for availing the cities amenities. Hence, this is creating pressure on the overall water quality of Dhaka city. The work intended to assess the groundwater standard in Mirpur area of Dhaka City, Bangladesh by analyzing eight (08) different physicochemical water quality parameters. In December 2023, six (06) separate water samples were taken throughout the dry season from six (06) sites across the area. The results showed that all sites had pH levels between 7.18 to 7.50, which is within acceptable ranges for drinking water quality and indicates neutral to slightly alkaline conditions. Total dissolved solids (TDS) continued to be far below safety limits (210–250 ppm), indicating that the water's mineral content was quite low. Electrical conductivity (EC) measurements fell within acceptable ranges(290-350 μS/cm), indicating suitable groundwater quality. Dissolved oxygen (DO) levels varied(3.7-9.3 mg/L), with some sites exhibiting satisfactory oxygenation while others raised concerns about potential water quality issues. Total hardness(TH)levels(330-900 mg/L)exceeded recommended limits(200-500 mg/L)at all sites, suggesting potential issues with water quality. However, chemical oxygen demand (COD) levels were minimal or zero(0-3 mg/L), indicating minimal organic pollution. Iron concentrations were generally low(0-0.05 mg/L).Total chlorine(TC)concentrations varied(0-0.03 mg/L)across sites.In summary, the study emphasizes how crucial it is to continuously monitor and regulate the quality of groundwater in order to guarantee the sustainability and safety of water resources in the Mirpur region.